Understanding Labor Market Discrimination against Transgender People: Evidence from a Double List Experiment and a Survey - Billur Aksoy; Christopher S. Carpenter; Dario Sansone (Institute of Labor Economics (IZA), 2022)
Using a US nationally representative sample and a double list experiment designed to elicit views free from social desirability bias, we find that anti-transgender labor market attitudes are significantly underreported. After correcting for this concealment, we report that 73 percent of people would be comfortable with a transgender manager and 74 percent support employment non-discrimination protection for transgender people. We also show that respondents severely underestimate the population level of support for transgender individuals in the workplace, and we find that labor market support for transgender people is significantly lower than support for gay, lesbian, and bisexual people. Our results provide timely evidence on workplace-related views toward transgender people and help us better understand employment discrimination against them.
Keywords: C90; J15; J71; K31; 330; labor market discrimination; transgender people; double list experiment